Laparoscopic Appendectomy VS Open Appendectomy at Jeddah National Hospital Saudi Arabia; A Comparative Study - Aftab Ahmed Soomro, Juwereya Memon, Rajab Gharno, Abdul Sattar Memon, Kashif Chana, Hamad Afzal Malik, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the laparoscopic appendectomy (LA) with open appendectomy (OA) in terms of operative time, complications, and hospital stay. Patients and Methods: This comparative study was done at Jeddah National Hospital, KSA. All the patients aged more than 12 years, both genders, and those who were admitted with appendicitis to the surgical department and underwent surgical treatment were included. The study duration was one year, from November 2019 to October 2020. All the patients were divided into two groups. Patients who underwent laparoscopic appendectomies were put in LA group, while those who underwent open appendectomies were kept in OA group. All the patients were observed during hospital stays and comparative treatment outcomes were observed in terms of the pain, number of hours required for the return of bowel function, operative time, infection and hospital stays. A study proforma was used for the data collection and SPSS version 26 was used for the data analysis. Results: A total of 100 cases were comparatively studied, and the overall age of the patients was 33.34+7.23 years. Males were dominant as compared to females. Average operating time was lower in LA group as 37.11+8.41 minutes, compared to the OA group 47.45+4.34 minutes (p-0.001). The average post-operative hospital stay was 1.88+0.62 days in LA group, compared to the OA group 2.14+0.90 days, without a significant difference (p-0.098). Post operative infection was statistically insignificant in both groups as one case in the LA group and in cases of the OA group (p-558). Conversion to an open procedure was required in one case with extensive cecal adhesions and retrocecal gangrenous appendicitis with local peritonitis. 70% patients of LA group, returned to their normal routine life within 10 days and the remaining started doing their normal activities within 15 days, while in the OA group, 60% of patients returned to normal activity and 40% returned to work after 20 days. No mortality was found in either group. Conclusion: Laparoscopic appendectomy was observed to be a time-saving procedure, which depends on skills, patient selection, and availability of the laparoscope. It is safe when compared to open appendectomy. It shortens the hospital stay, allows for an earlier return to oral feeding, normal routine work, and results in fewer post-operative complications.